Competence Over Cost: Reassessing the Determinants of Construction Safety Planning Quality - Puti Afifah Sholeha; Indri Hapsari Susilowati (Jurnal Penelitian Kesehatan SUARA FORIKES, 2026)
The assumption that financial investment is directly proportional to the quality of construction safety planning is commonly used as a basis for project budgeting. However, the persistently high rate of occupational accidents indicates a gap between cost allocation and the effectiveness of risk mitigation in practice. This study aimed to evaluate the relationship between the allocation of Construction Safety Management System costs and the quality of Construction Safety Plan documents, as well as to identify cost efficiency across construction work packages. This study employed a descriptive-analytical approach using document-based data obtained from Construction Safety Plan documents across several construction work packages. Document quality was assessed using a scoring method and further analyzed using a cost-effectiveness analysis approach to evaluate efficiency. The findings indicate that low-cost work packages are capable of producing high-quality Construction Safety Plan documents, while high-cost packages tend to be inefficient and fail to meet substantive performance evaluation criteria. These results suggest that planning quality is more influenced by personnel competence than by budget size. In conclusion, budget size does not necessarily guarantee compliance with construction safety standards. Therefore, safety planning evaluation should prioritize technical substance and regulatory compliance to enhance the effectiveness of worker protection.Keywords: cost effectiveness; construction safety plan; regulatory compliance; occupational safety